High-temperature binder for combination of multiple ceramic cores in preparation of ceramic cores with complex structure and preparation method thereof

CN122647251APending Publication Date: 2026-08-28AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610787923.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

此类复杂结构陶瓷型芯通常无法一次成型,需采用多个型芯部件组合粘接的方式制备,因此高温粘结剂的性能成为影响复杂结构陶瓷型芯成型质量和服役寿命的关键因素

Benefits of technology

(1)本发明的高温粘结剂采用复合溶胶基体、梯度级配耐火填料、纳米增强相及协同改性剂协同配合,各组分分工明确、协同作用,有效解决了现有粘结剂高温易开裂、粘结强度不足的问题,同时摒弃了传统粘结剂中易与合金液反应的低熔点元素,从源头避免了高温合金浇注过程中因低熔点元素与合金液反应而产生的叶片内腔凹坑、麻面等缺陷。复合溶胶基体确保粘结性和兼容性,梯度级配耐火填料提升致密性和高温耐火性能,纳米增强相(含两种纳米颗粒和四种晶须)通过桥接作用显著提升粘结强度和抗开裂能力,协同改性剂优化涂覆性和抗收缩能力,使粘结剂在1500-1800℃的高温环境下仍能保持优异的粘结强度和结构完整性,既满足复杂结构陶瓷型芯的高温服役需求,又保障了高端铸件的表面质量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647251A_ABST
    Figure CN122647251A_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature binder for multiple ceramic core combination in a complex structure ceramic core preparation process and a preparation method thereof. In the high-temperature binder, the proportions of various substances are as follows: 35-45 wt% of a composite sol matrix, 45-55 wt% of a gradient grading refractory filler, 3-8 wt% of a nano-enhanced phase and 2-7 wt% of a synergistic modifier. The preparation method comprises the following steps: preparing the composite sol matrix, the gradient grading refractory filler, a nano-enhanced dispersion liquid and the synergistic modifier; adding the gradient grading refractory filler, the nano-enhanced dispersion liquid and the synergistic modifier into a constant-temperature stirring kettle containing the composite sol matrix in sequence and stirring uniformly to obtain high-temperature binder initial materials; vacuum deaerating and low-temperature curing the high-temperature binder initial materials in sequence, and obtaining the high-temperature binder after cooling. The application realizes the dual improvement of the bonding strength and high-temperature stability, has good coating performance and forming adaptability, and is suitable for various ceramic cores which need to be combined and formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic core preparation technology, specifically relating to a high-temperature binder and preparation method for multi-core combination in the preparation process of complex structure ceramic cores. Background Technology

[0002] Ceramic cores are crucial components in investment casting, forming complex internal cavity structures such as aero-engine turbine blades, heavy-duty gas turbine blades, and precision mechanical parts. Their performance directly determines the dimensional accuracy and service reliability of the castings. With the rapid development of aerospace, high-end equipment manufacturing, and other technological fields, the requirements for the structural complexity of ceramic cores are constantly increasing. The application of complex ceramic core structures such as multi-walled cores, hollow cores, multi-layer rotary cores, variable-cycle composite cores, and hollow-edge cores is becoming increasingly widespread. These complex ceramic core structures typically cannot be formed in a single step and require the assembly and bonding of multiple core components. Therefore, the performance of the high-temperature binder becomes a key factor affecting the molding quality and service life of complex ceramic core structures.

[0003] Currently, existing high-temperature adhesives used for bonding ceramic cores mainly consist of a single sol (such as silica sol, alumina sol, etc.) or a single refractory filler, which have the following drawbacks: First, they have poor high-temperature stability, easily softening and cracking at temperatures above 1200℃, leading to detachment of the bonded area and failing to meet the service requirements of complex cores in high-temperature casting processes; second, they have insufficient bonding strength, especially at the joints of complex cores, where uneven stress can easily cause interface separation, affecting the overall structural integrity of the core; third, they have poor compatibility with the ceramic core matrix, and stress concentration easily occurs at the bonding interface, leading to... Fourth, poor coating and molding compatibility make it difficult to adapt to the irregular splicing surfaces of complex cores, and shrinkage deformation is likely to occur after drying and curing, further affecting the dimensional accuracy of the core; Fifth, in order to improve high-temperature adhesion, traditional binders usually add more low-melting-point elements (such as boron, lithium, sodium, etc.). These low-melting-point elements will react chemically with the alloy liquid during the high-temperature alloy casting process, generating impurities or causing abnormal local composition of the alloy liquid, which in turn forms defects such as pits and pitting in the inner cavity of the blade, seriously affecting the surface quality and service reliability of high-end castings such as aero-engine turbine blades.

[0004] Furthermore, existing binder preparation processes often employ simple mixing methods, leading to uneven dispersion of components and easy agglomeration of the reinforcing phase, thus failing to fully realize its reinforcing effect and further limiting the improvement of binder performance. Simultaneously, existing binder curing processes are mostly single high-temperature curing, which consumes a lot of energy and easily generates internal pores after curing, reducing bond strength and density. In addition, the introduction of low-melting-point elements introduces surface defects into the castings, further highlighting the inability of existing high-temperature binders to meet the needs of complex ceramic core structures. Therefore, developing a high-temperature binder that combines excellent high-temperature stability, high bond strength, good compatibility and molding adaptability, without introducing low-melting-point elements, has become an urgent problem to be solved in the field of complex ceramic core bonding technology. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention provides a high-temperature binder for multi-core combination in the preparation process of complex structure ceramic cores. The high-temperature binder contains the following components by mass percentage: 35-45 wt% composite sol matrix, 45-55 wt% graded refractory filler, 3-8 wt% nano-reinforcing phase, and 2-7 wt% synergistic modifier, with the sum of the contents of each component being 100 wt%.

[0006] Preferably, the composite sol matrix is ​​composed of silica sol, aluminum sol and yttrium sol, with the mass ratio of silica sol, aluminum sol and yttrium sol being 3-4:1.5-2:1; the solid content of silica sol is 30-40%, the solid content of aluminum sol is 25-35%, and the solid content of yttrium sol is 20-30%.

[0007] In this invention, silica sol has good adhesion and coating properties, aluminum sol can improve the high temperature strength and wear resistance of the binder, and yttrium sol can improve the compatibility between the binder and the ceramic core matrix. The three are combined to form a composite sol matrix. By adjusting the mass ratio of the three substances, the adhesion, high temperature stability and compatibility can be synergistically improved, laying the foundation for the high performance of the binder.

[0008] In any of the above embodiments, it is preferred that the graded refractory filler is composed of coarse refractory filler, medium refractory filler and fine refractory filler, the mass ratio of the coarse refractory filler, the medium refractory filler and the fine refractory filler is 1:2-2.5:1.2-1.8; the particle size ratio of the coarse refractory filler, the medium refractory filler and the fine refractory filler is 4-8:1.4-3.8:1, wherein the particle size of the fine refractory filler is 10-18μm.

[0009] In any of the above embodiments, preferably, the coarse refractory filler is quartz glass powder; the intermediate refractory filler is composed of white corundum powder and mullite powder, the mass ratio of white corundum powder to mullite powder is 1:1.5-2; the mass percentage of each substance in the fine refractory filler is 50-62 wt% zirconium silicate powder, 15-25 wt% yttrium oxide powder, 8-15 wt% hafnium oxide powder, 5-10 wt% neodymium oxide powder, and 2-8 wt% scandium oxide powder, the sum of the contents of each substance is 100 wt%.

[0010] In this invention, coarse-grade refractory filler enhances the skeletal strength and shrinkage resistance of the binder; medium-grade refractory filler fills the gaps between coarse-grade fillers, improving the compactness of the binder; and fine-grade refractory filler further fills the gaps, simultaneously improving the high-temperature refractory performance and interfacial bonding ability with the core matrix. This invention, through a gradient gradation design, enables each grade of refractory filler to form a dense packing structure, effectively reducing internal porosity in the binder, improving high-temperature stability and bonding strength, while also adapting to the coating requirements of complex core irregular splicing surfaces.

[0011] In any of the above embodiments, it is preferred that the mass percentage of each substance in the nano-reinforcing phase is 25-35 wt% nano-silica, 15-22 wt% nano-alumina, 12-18 wt% silica whiskers, 12-18 wt% alumina whiskers, 8-12 wt% mullite whiskers, and 8-12 wt% zirconium oxide whiskers, with the sum of the contents of each substance being 100 wt%.

[0012] In any of the above embodiments, preferably, the particle size of the nano-silica and the nano-alumina is 50-100 nm; the diameter of the silica whiskers and the alumina whiskers is controlled within the range of 0.1-0.5 μm and the length is controlled within the range of 1-10 μm; the diameter of the mullite whiskers and the zirconium oxide whiskers is controlled within the range of 0.5-1 μm and the length is controlled within the range of 10-20 μm.

[0013] In this invention, nano-silica and nano-alumina can fill the tiny pores inside the binder, improving its density; the four types of whiskers have excellent mechanical properties and high-temperature stability, preventing crack propagation through bridging, significantly improving the adhesive strength and crack resistance of the binder, and working synergistically with other components to further optimize the high-temperature performance of the binder; the control of nanoparticle purity (not less than 99.5%) and whisker size (diameter and length) can ensure the stable performance of the reinforcing effect, avoid the influence of impurities or improper size on the binder performance, and improve the adhesive strength and crack resistance of the binder.

[0014] In any of the above embodiments, preferably, the mass percentage of each substance in the synergistic modifier is 45-55 wt% mica powder, 10-20 wt% talc powder, 10-20 wt% silica powder, and 15-25 wt% hydroxypropyl methylcellulose, with the sum of the contents of each substance being 100 wt%; the particle size ratio of the mica powder, the talc powder, and the silica powder is 1:1.2-1.8:1.7-2.1, wherein the particle size of the mica powder is 20-25 μm.

[0015] In this invention, mica powder can improve the flexibility and shrinkage resistance of the adhesive and reduce deformation during the curing process; talc powder can improve the coatability and flowability of the adhesive, making it easier to coat evenly on complex core splicing surfaces; silica powder can enhance the high-temperature wear resistance and interfacial bonding strength of the adhesive; hydroxypropyl methylcellulose can adjust the viscosity of the adhesive, prevent component stratification, and at the same time improve the water retention of the adhesive, avoiding cracking during the drying process.

[0016] This invention also provides a method for preparing a high-temperature binder for multi-core assembly during the fabrication of complex-structure ceramic cores, the preparation method comprising the following steps in sequence: Step 1: Prepare the composite sol matrix, gradient-graded refractory filler, nano-reinforced dispersion, and synergistic modifier according to the preset material ratio and process parameters; Step 2: Slowly add the graded refractory filler into the constant temperature stirred tank containing the composite sol matrix while stirring, so that the graded refractory filler is evenly dispersed in the composite sol matrix. Step 3: Add the nano-reinforced dispersion to the constant temperature stirring vessel and continue stirring to ensure that all substances are evenly dispersed; Step 4: First reduce the stirring speed, then add the synergistic modifier to the constant temperature stirring vessel and continue stirring to make the substances evenly dispersed, thus obtaining the initial material of the high temperature binder; Step 5: First, put the high-temperature adhesive raw material into a vacuum degassing machine for vacuum degassing, and then put the vacuum degassed high-temperature adhesive raw material into an oven for low-temperature curing. After the low-temperature curing is completed, take it out and let it cool naturally to room temperature to obtain the high-temperature adhesive.

[0017] Preferably, in step one, the preparation process of the composite sol matrix is ​​as follows: silica sol, aluminum sol, and yttrium sol are placed in a constant-temperature stirred tank and stirred and mixed at a temperature of 25-35℃, a stirring speed of 300-500 rpm, and a stirring time of 30-60 min to ensure uniform dispersion of the substances and obtain the composite sol matrix, which is then kept at a constant temperature in the stirred tank for later use. This process ensures thorough mixing of the three sols through constant-temperature stirring, avoiding stratification and laying the foundation for subsequent component composites. The control of stirring temperature, stirring speed, and stirring time prevents sol aggregation and ensures the stability of the composite sol matrix.

[0018] In any of the above schemes, preferably, in step one, the preparation process of the gradient-graded refractory filler is as follows: The coarse-grade, medium-grade, and fine-grade refractory fillers are placed in a mixer and stirred. The stirring temperature is room temperature, the stirring speed is 800-1000 rpm, and the stirring time is 20-30 minutes, ensuring thorough mixing of each grade of refractory filler to obtain the gradient-graded refractory filler. This high-speed mixing process ensures uniform mixing of refractory fillers of different particle sizes and types, forming a stable gradient-graded structure, avoiding local agglomeration, and improving the packing density of each grade of refractory filler.

[0019] In any of the above embodiments, preferably, in step one, the preparation process of the nano-reinforced dispersion is as follows: The various substances of the nano-reinforcement phase, deionized water, and a dispersant are placed in an ultrasonic container for ultrasonic dispersion. The amount of deionized water added is 3-5 times the mass of the nano-reinforcement phase. The dispersant is sodium dodecylbenzenesulfonate, added at 0.5-1 wt% of the mass of the nano-reinforcement phase. The ultrasonic power is 300-500 W, and the ultrasonic dispersion time is 20-30 min, ensuring uniform dispersion of the substances to obtain the nano-reinforced dispersion. This process, through ultrasonic dispersion combined with the action of the dispersant, effectively prevents the agglomeration of the nano-reinforcement phase, ensuring its uniform dispersion in deionized water and fully utilizing its reinforcing effect. Controlling the ultrasonic power and ultrasonic dispersion time avoids whisker breakage, guaranteeing the reinforcing effect.

[0020] In any of the above schemes, it is preferred that, in step one, the preparation process of the synergistic modifier is as follows: mica powder, talc powder, silica powder and hydroxypropyl methylcellulose are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 500-800 rpm, and the stirring time is 20-30 min, so that the substances are mixed evenly to obtain the synergistic modifier.

[0021] In any of the above schemes, it is preferred that, in step two, the addition rate of the gradient-graded refractory filler is 5-10 g / min, the stirring temperature is 25-35℃, the stirring speed is 600-800 rpm, and the stirring time is 40-60 min.

[0022] In any of the above schemes, it is preferred that, in step three, after adding the nano-reinforced dispersion, the mixture is stirred for 30-40 minutes.

[0023] In any of the above schemes, it is preferred that in step four, the stirring speed is reduced to 400-600 rpm, and after adding the synergistic modifier, stirring is continued for 20-30 minutes.

[0024] In any of the above schemes, the preferred method is that, in step five, the vacuum degassing process parameters for the high-temperature adhesive precursor are: vacuum degree of -0.08 to -0.09 MPa, degassing time of 15-25 min, and stirring once every 5 min during the vacuum degassing process, with each stirring lasting 5 min; the low-temperature curing process parameters for the high-temperature adhesive precursor are: curing temperature of 80-100℃, and curing time of 2-3 h.

[0025] In this invention, steps two through four employ a step-by-step addition and gradient stirring method. First, the gradient-graded refractory filler is added and stirred at high speed to ensure that each level of refractory filler is uniformly dispersed in the composite sol matrix. Then, the nano-reinforced dispersion is added, and stirring continues to ensure uniform distribution of nanoparticles and whiskers. Finally, the synergistic modifier is added and the stirring speed is reduced to avoid damage to the modifier, while ensuring that all components are fully composited to form a stable binder initial material. The addition rate of the gradient-graded refractory filler is controlled at 5-10 g / min, which effectively prevents filler agglomeration and further improves dispersion uniformity.

[0026] In step five, vacuum degassing effectively removes air bubbles from the initial adhesive material, preventing internal pores from forming after curing and improving the density of the adhesive. During vacuum degassing, the adhesive is stirred every 5 minutes for 5 minutes each time to ensure thorough degassing. Low-temperature curing allows the adhesive to cure slowly, reducing shrinkage, deformation, and cracking during the curing process. After cooling to room temperature, a stable adhesive product is formed. Compared with the traditional single high-temperature curing process, energy consumption is significantly reduced, and the curing effect is better.

[0027] This invention also provides the application of the aforementioned high-temperature adhesive, which can be used for the combined molding of multi-layer wall cores, hollow cores, multi-layer rotary cores, variable circulation combined cores, and hollow edge plate cores. In use, the high-temperature adhesive is applied to the bonding areas of the core with a thickness of 0.1-0.3 mm. Then, the core components are assembled and cured at 120-150℃ for 1-2 hours to complete the assembly. This application method ensures that the high-temperature adhesive fully bonds to the core substrate, forming a bonded area without obvious interface defects. It is suitable for the service requirements of complex ceramic core structures. Controlling the coating thickness avoids shrinkage and deformation due to excessive adhesive or weak bonding due to insufficient adhesive. The curing parameter settings ensure optimal bonding results.

[0028] This invention provides a high-temperature binder and preparation method for multi-core assembly in the fabrication of complex ceramic cores. It solves the technical problems of existing binders in the fabrication of complex ceramic cores, such as easy cracking at high temperatures, insufficient bonding strength, poor compatibility with the core matrix, easy introduction of low melting point elements leading to defects such as pits and rough surfaces in the blade cavity, and inability to meet the molding requirements of complex ceramic cores such as multi-walled cores, hollow cores, and multi-layer rotary cores, resulting in low core molding accuracy and poor service stability.

[0029] The high-temperature binder of this invention uses a composite sol as a matrix, combined with gradient-graded refractory fillers, nano-reinforcing phases, and synergistic modifiers. The synergistic effect of these components achieves a dual improvement in bonding strength and high-temperature stability, while also possessing excellent coatability and moldability. The preparation method employs a stepwise dispersion, gradient compounding, and low-temperature curing process, which is simple, controllable, and energy-efficient. It can be widely applied to various ceramic cores requiring assembly, such as multi-walled cores, hollow cores, multi-layer rotary cores, variable-cycle combined cores, and hollow edge plate cores. There are no obvious interface defects at the bonding sites, and it maintains excellent bonding strength and structural integrity even at high temperatures of 1500-1800℃. This significantly improves the molding quality and service life of complex ceramic core structures, demonstrating high practical value and promising industrial application prospects.

[0030] The present invention relates to a high-temperature binder and preparation method for multi-core assembly in the fabrication of complex-structure ceramic cores, which has the following beneficial effects: (1) The high-temperature binder of the present invention adopts a composite sol matrix, a gradient-graded refractory filler, a nano-reinforcing phase and a synergistic modifier in synergy. Each component has a clear division of labor and synergistic effect, which effectively solves the problems of easy cracking and insufficient bonding strength of existing binders at high temperatures. At the same time, it eliminates the low-melting-point elements in traditional binders that are easy to react with the alloy liquid, thus avoiding defects such as pits and rough surfaces in the blade cavity caused by the reaction of low-melting-point elements with the alloy liquid during the high-temperature alloy casting process. The composite sol matrix ensures adhesion and compatibility, the gradient-graded refractory filler improves density and high-temperature refractory performance, the nano-reinforcing phase (containing two kinds of nanoparticles and four kinds of whiskers) significantly improves bonding strength and crack resistance through bridging effect, and the synergistic modifier optimizes coating and anti-shrinkage ability, so that the binder can still maintain excellent bonding strength and structural integrity in the high-temperature environment of 1500-1800℃, which not only meets the high-temperature service requirements of complex ceramic cores, but also ensures the surface quality of high-end castings.

[0031] (2) The high-temperature adhesive of the present invention has good compatibility with the ceramic core substrate, and the bonding interface has no obvious defects. It can effectively reduce the stress concentration at the interface and significantly improve the molding accuracy of complex ceramic cores. At the same time, it has good coating properties and fluidity. It can be adapted to the irregular splicing surface of complex cores such as multi-layer wall cores, hollow cores, and multi-layer rotary cores. The coating is uniform and there is no obvious shrinkage deformation after curing, which further ensures the molding quality of the core.

[0032] (3) The preparation method of the present invention adopts stepwise dispersion, gradient composite and low temperature curing process. The process is simple and controllable. Compared with the traditional preparation process, it does not require complicated equipment, has low energy consumption, and ensures uniform dispersion of each component by ultrasonic dispersion, gradient stirring and other methods, avoids the agglomeration of nano-reinforced phase, gives full play to the performance advantages of each component, has high preparation efficiency, and is suitable for large-scale industrial production.

[0033] (4) The high-temperature adhesive of the present invention has a wide range of applications and can be widely used in various ceramic cores that need to be assembled, such as multi-layer wall cores, hollow cores, multi-layer rotary cores, variable circulation combined cores, and hollow edge plate cores. The bonding effect is stable and can significantly improve the service life of complex structure ceramic cores. It has extremely high practical value and industrial application prospects. Attached Figure Description

[0034] Figure 1 A photograph of a high-temperature binder prepared according to a preferred embodiment of the high-temperature binder and preparation method for multi-core assembly in the preparation process of complex structure ceramic cores of the present invention; Figure 2 To adopt Figure 1 Photograph of the ceramic core bonded with the high-temperature adhesive prepared in the example shown; Figure 3 This is a photograph of the inner cavity of the blade after casting in Example 1 (no reaction in the inner cavity). Figure 4 This is a photograph of the inner cavity of the blade after casting (showing an inner cavity reaction). Detailed Implementation

[0035] To further understand the invention, the following detailed description of the invention will be provided in conjunction with specific embodiments.

[0036] Example 1: According to a preferred embodiment of the high-temperature binder for multi-core combination in the preparation process of complex structure ceramic cores of the present invention, the mass percentage of each substance in the high-temperature binder is 40wt% of composite sol matrix, 50wt% of gradient graded refractory filler, 5wt% of nano-reinforcing phase, and 5wt% of synergistic modifier.

[0037] The composite sol matrix is ​​composed of silica sol, aluminum sol and yttrium sol, with a mass ratio of silica sol, aluminum sol and yttrium sol of 3.5:1.8:1; the solid content of silica sol is 35%, the solid content of aluminum sol is 30%, and the solid content of yttrium sol is 25%.

[0038] The graded refractory filler is composed of coarse refractory filler, medium refractory filler and fine refractory filler, with a mass ratio of 1:2.2:1.5 for the coarse refractory filler, medium refractory filler and fine refractory filler; and a particle size ratio of 6:2.6:1 for the coarse refractory filler, medium refractory filler and fine refractory filler, wherein the particle size of the fine refractory filler is 14μm.

[0039] The coarse refractory filler is quartz glass powder; the intermediate refractory filler is composed of white corundum powder and mullite powder, with a mass ratio of white corundum powder to mullite powder of 1:1.8; the mass percentage of each substance in the fine refractory filler is 56 wt% zirconium silicate powder, 20 wt% yttrium oxide powder, 12 wt% hafnium oxide powder, 7 wt% neodymium oxide powder, and 5 wt% scandium oxide powder.

[0040] The mass percentages of each substance in the nano-reinforcing phase are as follows: 30 wt% nano-silica, 20 wt% nano-alumina, 15 wt% silica whiskers, 15 wt% alumina whiskers, 10 wt% mullite whiskers, and 10 wt% zirconium oxide whiskers. The particle size of both the nano-silica and nano-alumina is 75 nm. The diameters of the silica and alumina whiskers are controlled within the range of 0.1-0.5 μm, and their lengths within the range of 1-10 μm. The diameters of the mullite and zirconium oxide whiskers are controlled within the range of 0.5-1 μm, and their lengths within the range of 10-20 μm.

[0041] The mass percentages of each substance in the synergistic modifier are as follows: mica powder 50wt%, talc powder 15wt%, silica powder 15wt%, and hydroxypropyl methylcellulose 20wt%. The particle size ratio of the mica powder, talc powder, and silica powder is 1:1.5:1.9, wherein the particle size of the mica powder is 22μm.

[0042] This embodiment also provides a method for preparing a high-temperature binder for multi-core assembly during the fabrication of complex structure ceramic cores. The preparation method includes the following steps in sequence: Step 1: Prepare the composite sol matrix, gradient-graded refractory filler, nano-reinforced dispersion, and synergistic modifier according to the preset material ratio and process parameters; Step 2: Slowly add the graded refractory filler into the constant temperature stirred tank containing the composite sol matrix while stirring, so that the graded refractory filler is evenly dispersed in the composite sol matrix. Step 3: Add the nano-reinforced dispersion to the constant temperature stirring vessel and continue stirring to ensure that all substances are evenly dispersed; Step 4: First reduce the stirring speed, then add the synergistic modifier to the constant temperature stirring vessel and continue stirring to make the substances evenly dispersed, thus obtaining the initial material of the high temperature binder; Step 5: First, put the high-temperature adhesive raw material into a vacuum degassing machine for vacuum degassing, and then put the vacuum degassed high-temperature adhesive raw material into an oven for low-temperature curing. After the low-temperature curing is completed, take it out and let it cool naturally to room temperature to obtain the high-temperature adhesive.

[0043] In step one, the preparation process of the composite sol matrix is ​​as follows: silica sol, aluminum sol and yttrium sol are placed in a constant temperature stirring vessel and stirred and mixed. The stirring temperature is 30°C, the stirring speed is 400 rpm, and the stirring time is 45 min, so that the substances are evenly dispersed to obtain the composite sol matrix, which is then kept warm in the constant temperature stirring vessel for later use.

[0044] The preparation process of the gradient-graded refractory filler is as follows: the materials of coarse refractory filler, medium refractory filler and fine refractory filler are put into a mixer for stirring and mixing. The stirring temperature is room temperature, the stirring speed is 900 rpm and the stirring time is 25 min, so that the graded refractory fillers are fully mixed to obtain the gradient-graded refractory filler.

[0045] The preparation process of the nano-reinforced dispersion is as follows: each substance of the nano-reinforced phase, deionized water and dispersant are placed in an ultrasonic container for ultrasonic dispersion. The amount of deionized water added is 4 times the mass of the nano-reinforced phase, and the dispersant is sodium dodecylbenzenesulfonate, which is added at 0.8 wt% of the mass of the nano-reinforced phase. The ultrasonic power is 400 W and the ultrasonic dispersion time is 25 min to make the substances uniformly dispersed and obtain the nano-reinforced dispersion.

[0046] The preparation process of the synergistic modifier is as follows: mica powder, talc powder, silica powder and hydroxypropyl methylcellulose are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 650 rpm and the stirring time is 25 min, so that the substances are mixed evenly to obtain the synergistic modifier.

[0047] In step two, the gradient refractory filler is added at a rate of 8 g / min, the stirring temperature is 30℃, the stirring speed is 700 rpm, and the stirring time is 50 min.

[0048] In step three, after adding the nano-reinforced dispersion, continue stirring for 35 minutes.

[0049] In step four, the stirring speed is reduced to 500 rpm, and the synergistic modifier is added and stirring is continued for 25 minutes.

[0050] In step five, the vacuum degassing process parameters for the high-temperature adhesive precursor are: vacuum degree -0.08MPa, degassing time 20min, and stirring once every 5min during the vacuum degassing process, each stirring lasting 5min; the low-temperature curing process parameters for the high-temperature adhesive precursor are: curing temperature 90℃, curing time 2.5h.

[0051] The high-temperature adhesive prepared in this embodiment can be used for the assembly molding of multi-layer wall cores, hollow cores, multi-layer rotary cores, variable circulation combined cores, and hollow edge plate cores. In use, the high-temperature adhesive is applied to the bonding areas of the core, with a coating thickness of 0.1-0.3 mm. Then, the core components are assembled and cured at 120-150℃ for 1-2 hours to complete the assembly molding. The high-temperature adhesive prepared in this embodiment is as follows... Figure 1 As shown, the ceramic core bonded using this high-temperature adhesive is as follows: Figure 2 As shown.

[0052] This embodiment has the following beneficial effects: (1) The high-temperature binder adopts a composite sol matrix, gradient graded refractory filler, nano-reinforcing phase and synergistic modifier in synergy, which effectively solves the problems of easy cracking and insufficient bonding strength of existing binders at high temperature. At the same time, it eliminates the low melting point elements in traditional binders that are easy to react with the alloy liquid, thus avoiding defects such as pits and pitting in the blade cavity caused by the reaction of low melting point elements with the alloy liquid during the high-temperature alloy casting process. (2) The high-temperature binder has good compatibility with the ceramic core matrix, and there are no obvious defects at the bonding interface, which can effectively reduce the stress concentration at the interface. It also has good coatability and fluidity. (3) The step-by-step dispersion, gradient composite and low-temperature curing process is adopted. The process is simple and controllable, no complex equipment is required, the energy consumption is low, and it is suitable for large-scale industrial production.

[0053] Example 2: Another preferred embodiment of the high-temperature binder and preparation method for multi-core combination in the preparation process of complex structure ceramic cores according to the present invention is basically the same as that in Embodiment 1 in terms of raw materials, preparation method, technical principle, and beneficial effects, except that: The high-temperature binder comprises the following components in proportion: 35 wt% composite sol matrix, 55 wt% graded refractory filler, 3 wt% nano-reinforcing phase, and 7 wt% synergistic modifier.

[0054] The mass ratio of silica sol, aluminum sol, and yttrium sol in the composite sol matrix is ​​3:1.5:1; the solid content of the silica sol is 30%, the solid content of the aluminum sol is 25%, and the solid content of the yttrium sol is 20%.

[0055] The mass ratio of coarse refractory filler, medium refractory filler, and fine refractory filler in the graded refractory filler is 1:2:1.2, and the particle size ratio of coarse refractory filler, medium refractory filler, and fine refractory filler is 4:1.4:1, wherein the particle size of the fine refractory filler is 10μm.

[0056] The coarse refractory filler is quartz glass powder; the mass ratio of white corundum powder to mullite powder in the intermediate refractory filler is 1:1.5; the proportions of each substance in the fine refractory filler are 53wt% zirconium silicate powder, 25wt% yttrium oxide powder, 9wt% hafnium oxide powder, 10wt% neodymium oxide powder, and 3wt% scandium oxide powder.

[0057] The composition of the nano-reinforcing phase is as follows: 28 wt% nano-silica, 22 wt% nano-alumina, 12 wt% silica whiskers, 18 wt% alumina whiskers, 8 wt% mullite whiskers, and 12 wt% zirconium oxide whiskers. The particle size of both the nano-silica and the nano-alumina is 50 nm.

[0058] The proportions of each substance in the synergistic modifier are as follows: mica powder 45wt%, talc powder 20wt%, silica powder 10wt%, and hydroxypropyl methylcellulose 25wt%; the particle size ratio of the mica powder, talc powder, and silica powder is 1:1.2:1.7, wherein the particle size of the mica powder is 20μm.

[0059] In step one, the preparation process of the composite sol matrix is ​​as follows: silica sol, aluminum sol and yttrium sol are placed in a constant temperature stirring vessel and stirred and mixed at a stirring temperature of 25°C, a stirring speed of 300 rpm and a stirring time of 30 min to ensure that the substances are uniformly dispersed.

[0060] The preparation process of the graded refractory filler is as follows: coarse refractory filler, medium refractory filler and fine refractory filler are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 800 rpm and the stirring time is 20 min to ensure that the graded refractory fillers are fully mixed.

[0061] The preparation process of the nano-reinforced dispersion is as follows: the nano-reinforced phase, deionized water and dispersant are placed in an ultrasonic container for ultrasonic dispersion. The amount of deionized water added is 3 times the mass of the nano-reinforced phase, the amount of dispersant added is 0.5 wt% of the mass of the nano-reinforced phase, the ultrasonic power is 300W, and the ultrasonic dispersion time is 20min, so that the substances are uniformly dispersed.

[0062] The preparation process of the synergistic modifier is as follows: mica powder, talc powder, silicon powder and hydroxypropyl methylcellulose are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 500 rpm and the stirring time is 20 min to make the substances evenly mixed.

[0063] In step two, the gradient gradation refractory filler is added at a rate of 5 g / min, the stirring temperature is 25℃, the stirring speed is 600 rpm, and the stirring time is 40 min.

[0064] In step three, after adding the nano-reinforced dispersion, continue stirring for 30 minutes.

[0065] In step four, the stirring speed is reduced to 400 rpm, and the synergistic modifier is added and stirring is continued for 20 minutes.

[0066] In step five, the vacuum degassing process parameters for the high-temperature adhesive precursor are: vacuum degree -0.08MPa, degassing time 15min; and the low-temperature curing process parameters for the high-temperature adhesive precursor are: curing temperature 80℃, curing time 2h.

[0067] Example 3: Another preferred embodiment of the high-temperature binder and preparation method for multi-core combination in the preparation process of complex structure ceramic cores according to the present invention is basically the same as that in Embodiment 1 in terms of raw materials, preparation method, technical principle, and beneficial effects, except that: The high-temperature binder comprises the following components in proportion: 45 wt% composite sol matrix, 45 wt% graded refractory filler, 8 wt% nano-reinforcing phase, and 2 wt% synergistic modifier.

[0068] The mass ratio of silica sol, aluminum sol, and yttrium sol in the composite sol matrix is ​​4:2:1; the solid content of the silica sol is 40%, the solid content of the aluminum sol is 35%, and the solid content of the yttrium sol is 30%.

[0069] The mass ratio of coarse refractory filler, medium refractory filler, and fine refractory filler in the graded refractory filler is 1:2.5:1.8, and the particle size ratio of coarse refractory filler, medium refractory filler, and fine refractory filler is 8:3.8:1, wherein the particle size of the fine refractory filler is 18μm.

[0070] The coarse refractory filler is quartz glass powder; the mass ratio of white corundum powder to mullite powder in the intermediate refractory filler is 1:2; the proportions of each substance in the fine refractory filler are 59wt% zirconium silicate powder, 15wt% yttrium oxide powder, 14wt% hafnium oxide powder, 5wt% neodymium oxide powder, and 7wt% scandium oxide powder.

[0071] The composition of the nano-reinforcing phase is as follows: 35 wt% nano-silica, 15 wt% nano-alumina, 18 wt% silica whiskers, 12 wt% alumina whiskers, 12 wt% mullite whiskers, and 8 wt% zirconium oxide whiskers. The particle size of both the nano-silica and the nano-alumina is 100 nm.

[0072] The proportions of each substance in the synergistic modifier are as follows: mica powder 55wt%, talc powder 10wt%, silica powder 20wt%, and hydroxypropyl methylcellulose 15wt%; the particle size ratio of the mica powder, talc powder, and silica powder is 1:1.8:2.1, wherein the particle size of the mica powder is 25μm.

[0073] In step one, the preparation process of the composite sol matrix is ​​as follows: silica sol, aluminum sol and yttrium sol are placed in a constant temperature stirring vessel and stirred and mixed at a stirring temperature of 35°C, a stirring speed of 500 rpm and a stirring time of 60 min to ensure that the substances are uniformly dispersed.

[0074] The preparation process of the graded refractory filler is as follows: coarse refractory filler, medium refractory filler and fine refractory filler are put into a mixer for stirring and mixing. The stirring temperature is room temperature, the stirring speed is 1000 rpm and the stirring time is 30 min, so that the graded refractory fillers are fully mixed.

[0075] The preparation process of the nano-reinforced dispersion is as follows: the nano-reinforced phase, deionized water and dispersant are placed in an ultrasonic container for ultrasonic dispersion. The amount of deionized water added is 5 times the mass of the nano-reinforced phase, the amount of dispersant added is 1 wt% of the mass of the nano-reinforced phase, the ultrasonic power is 500W, and the ultrasonic dispersion time is 30min, so that the substances are uniformly dispersed.

[0076] The preparation process of the synergistic modifier is as follows: mica powder, talc powder, silica powder and hydroxypropyl methylcellulose are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 800 rpm and the stirring time is 30 min to make the substances evenly mixed.

[0077] In step two, the gradient gradation refractory filler is added at a rate of 10 g / min, the stirring temperature is 35℃, the stirring speed is 800 rpm, and the stirring time is 60 min.

[0078] In step three, after adding the nano-reinforced dispersion, continue stirring for 40 minutes.

[0079] In step four, the stirring speed is reduced to 600 rpm, and the synergistic modifier is added and stirring is continued for 30 minutes.

[0080] In step five, the vacuum degassing process parameters for the high-temperature adhesive precursor are: vacuum degree -0.09MPa, degassing time 25min; and the low-temperature curing process parameters for the high-temperature adhesive precursor are: curing temperature 100℃, curing time 3h.

[0081] Comparative Example 1: The binder in this comparative example comprises the following components: 40 wt% composite sol matrix, 53 wt% graded refractory filler, and 7 wt% synergistic modifier, and does not contain a nano-reinforcing phase. The composition, proportions, preparation processes of the composite sol matrix, graded refractory filler, and synergistic modifier, as well as the preparation process of the binder, are basically the same as in Example 1.

[0082] Comparative Example 2: The binder in this comparative example comprises the following components: 40 wt% composite sol matrix, 50 wt% single-particle-size refractory filler, 5 wt% nano-reinforcing phase, and 5 wt% synergistic modifier. The refractory filler is white corundum powder with a particle size of 35 μm. The composition, proportions, preparation processes of the composite sol matrix, nano-reinforcing phase, and synergistic modifier, as well as the preparation process of the binder, are basically the same as in Example 1.

[0083] Comparative Example 3: The binder in this comparative example comprises the following components: 36 wt% composite sol matrix, 48 wt% graded refractory filler, 5 wt% nano-reinforcing phase, 4 wt% synergistic modifier, and 7 wt% boron powder (a low-melting-point element). The boron powder has a particle size of 25 μm and is added together with the synergistic modifier. The components, proportions, preparation processes of the composite sol matrix, graded refractory filler, nano-reinforcing phase, and synergistic modifier, as well as the preparation process of the binder, are basically the same as in Example 1.

[0084] Performance tests were conducted on the high-temperature binders prepared in the above embodiments and comparative examples, as well as on the existing conventional high-temperature binders (control group). The test conditions, environment, and equipment were all identical. The test results are shown in Table 1. A photograph of the blade's internal cavity after casting in Example 1 is shown below. Figure 3 As shown, no internal cavity reaction is visible; the photograph of the blade's internal cavity after casting in Comparative Example 3 is shown below. Figure 4 As shown, there is an internal cavity reaction.

[0085] The test items and test methods are as follows: (1) High-temperature bonding strength: Apply adhesive to the bonding parts of the ceramic core sample with a coating thickness of 0.2 mm, assemble the core components, and cure at 135℃ for 1.5 h to complete the assembly. Use a universal testing machine to test the bonding strength at 1600℃. Test 3 samples in each group and take the average value.

[0086] (2) High temperature stability: The bonded sample was placed in a high temperature furnace at 1800℃ for 2 hours and cooled to room temperature. The sample was observed to see if it cracked or deformed and its appearance was recorded.

[0087] (3) Compatibility: After the adhesive is applied to the surface of the ceramic core and cured and strengthened at high temperature, the bonding interface is observed under a microscope to determine whether there are interface defects.

[0088] (4) Coating properties: Apply the adhesive to the complex irregular splicing surface, observe the coating uniformity and flowability, and determine whether it is suitable for the coating requirements of complex cores.

[0089] From Table 1 and Figure 3 , Figure 4The comparison shows that the binders prepared in the three embodiments have significantly higher high-temperature bonding strength than the binders in the comparative and control groups. They can still maintain good stability at a high temperature of 1600℃, without cracking or deformation. They have good compatibility with the ceramic core matrix, no interface defects, excellent coatability, and can be adapted to complex irregular splicing surfaces. At the same time, the binders in the three embodiments do not introduce any low-melting-point elements, which effectively avoids defects such as pits and rough surfaces in the blade cavity caused by element reactions during the high-temperature alloy casting process, and fully meets the quality requirements of the assembly molding of complex ceramic cores and high-end castings.

[0090] Comparative Example 1, lacking a nano-reinforcing phase, exhibited a significant decrease in high-temperature bond strength compared to the Example 1, and slight cracking also occurred. This demonstrates that the bridging effect of the nano-reinforcing phase is crucial for improving bond strength and crack resistance. Comparative Example 2, without gradient-graded refractory filler, showed a significant decrease in high-temperature bond strength compared to the Example 1, with interfacial gaps and slight deformation. This indicates that the gradient-graded design can effectively improve the compactness, compatibility, and high-temperature stability of the binder. Comparative Example 3 introduced a low-melting-point element (boron powder). Although its high-temperature bond strength decreased less, numerous pits and rough surfaces appeared on the casting surface after casting. This shows that introducing low-melting-point elements into the binder has significant drawbacks, while highlighting the advanced design of the Example 1, which avoids low-melting-point elements, effectively ensuring the surface quality of high-end castings.

[0091] The raw materials used in the above embodiments and comparative examples were purchased from Aladdin Reagent Co., Ltd. and Sinopharm Chemical Reagent Co., Ltd.

[0092] Special Note: The technical solution of this invention involves numerous parameters, and the synergistic effects between these parameters must be comprehensively considered to achieve the beneficial effects and significant progress of this invention. Furthermore, the value ranges of each parameter in the technical solution were obtained through extensive experimentation. For each parameter and the combinations thereof, the inventors have recorded a large amount of experimental data; however, due to space limitations, the specific experimental data is not disclosed here.

[0093] It will be readily understood by those skilled in the art that this invention includes any combination of the inventive description and specific embodiments outlined in the foregoing specification, as well as the various parts shown in the accompanying drawings. Due to space limitations and for the sake of brevity, not all of these combinations have been described in detail. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A high-temperature binder for assembling multiple cores in the fabrication of complex ceramic cores, characterized in that, The high-temperature binder comprises the following components by mass percentage: 35-45 wt% composite sol matrix, 45-55 wt% graded refractory filler, 3-8 wt% nano-reinforcing phase, and 2-7 wt% synergistic modifier, with a total content of 100 wt%.

2. The high-temperature binder for multi-core assembly in the preparation process of complex structure ceramic cores according to claim 1, characterized in that, The composite sol matrix is ​​composed of silica sol, aluminum sol and yttrium sol, with a mass ratio of silica sol, aluminum sol and yttrium sol of 3-4:1.5-2:1; the solid content of silica sol is 30-40%, the solid content of aluminum sol is 25-35%, and the solid content of yttrium sol is 20-30%.

3. The high-temperature binder for multi-core assembly in the preparation process of complex structure ceramic cores according to claim 2, characterized in that, The graded refractory filler is composed of coarse refractory filler, medium refractory filler and fine refractory filler. The mass ratio of the coarse refractory filler, the medium refractory filler and the fine refractory filler is 1:2-2.5:1.2-1.

8. The particle size ratio of the coarse refractory filler, the medium refractory filler and the fine refractory filler is 4-8:1.4-3.8:1, wherein the particle size of the fine refractory filler is 10-18μm.

4. The high-temperature binder for multi-core assembly in the preparation process of complex structure ceramic cores according to claim 3, characterized in that, The coarse refractory filler is quartz glass powder; the intermediate refractory filler is composed of white corundum powder and mullite powder, with a mass ratio of white corundum powder to mullite powder of 1:1.5-2; the fine refractory filler contains the following mass percentages of zirconium silicate powder 50-62 wt%, yttrium oxide powder 15-25 wt%, hafnium oxide powder 8-15 wt%, neodymium oxide powder 5-10 wt%, and scandium oxide powder 2-8 wt%, with a total content of 100 wt%.

5. The high-temperature binder for multi-core assembly in the preparation process of complex structure ceramic cores according to claim 4, characterized in that, The mass percentage of each substance in the nano-reinforcing phase is as follows: 25-35 wt% nano-silica, 15-22 wt% nano-alumina, 12-18 wt% silica whiskers, 12-18 wt% alumina whiskers, 8-12 wt% mullite whiskers, and 8-12 wt% zirconium oxide whiskers, with a total content of 100 wt%.

6. The high-temperature binder for multi-core assembly in the preparation of complex structure ceramic cores according to claim 5, characterized in that, The particle size of the nano-silica and the nano-alumina is 50-100 nm; the diameter of the silica whiskers and the alumina whiskers is controlled within the range of 0.1-0.5 μm and the length is controlled within the range of 1-10 μm; the diameter of the mullite whiskers and the zirconium oxide whiskers is controlled within the range of 0.5-1 μm and the length is controlled within the range of 10-20 μm.

7. The high-temperature binder for multi-core assembly in the preparation process of complex structure ceramic cores according to claim 6, characterized in that, The mass percentage of each substance in the synergistic modifier is as follows: mica powder 45-55 wt%, talc powder 10-20 wt%, silica powder 10-20 wt%, and hydroxypropyl methylcellulose 15-25 wt%, with a total content of 100 wt%. The particle size ratio of the mica powder, talc powder, and silica powder is 1:1.2-1.8:1.7-2.1, wherein the particle size of the mica powder is 20-25 μm.

8. A method for preparing a high-temperature binder for multi-core assembly in the fabrication of complex-structure ceramic cores according to any one of claims 1-7, characterized in that, The preparation method includes the following steps in sequence: Step 1: Prepare the composite sol matrix, gradient-graded refractory filler, nano-reinforced dispersion, and synergistic modifier according to the preset material ratio and process parameters; Step 2: Slowly add the graded refractory filler into the constant temperature stirred tank containing the composite sol matrix while stirring, so that the graded refractory filler is evenly dispersed in the composite sol matrix. Step 3: Add the nano-reinforced dispersion to the constant temperature stirring vessel and continue stirring to ensure that all substances are evenly dispersed; Step 4: First reduce the stirring speed, then add the synergistic modifier to the constant temperature stirring vessel and continue stirring to make the substances evenly dispersed, thus obtaining the initial material of the high temperature binder; Step 5: First, put the high-temperature adhesive raw material into a vacuum degassing machine for vacuum degassing, and then put the vacuum degassed high-temperature adhesive raw material into an oven for low-temperature curing. After the low-temperature curing is completed, take it out and let it cool naturally to room temperature to obtain the high-temperature adhesive.

9. The method for preparing a high-temperature binder for multi-core assembly during the fabrication of complex-structure ceramic cores according to claim 8, characterized in that, In step one, the preparation process of the composite sol matrix is ​​as follows: silica sol, aluminum sol and yttrium sol are placed in a constant temperature stirring tank and stirred and mixed. The stirring temperature is 25-35℃, the stirring speed is 300-500rpm, and the stirring time is 30-60min, so that the substances are evenly dispersed to obtain the composite sol matrix, which is then kept warm in the constant temperature stirring tank for later use. The preparation process of the gradient-graded refractory filler is as follows: the materials of coarse refractory filler, medium refractory filler and fine refractory filler are put into a mixer for stirring and mixing. The stirring temperature is room temperature, the stirring speed is 800-1000 rpm, and the stirring time is 20-30 min, so that the graded refractory fillers are fully mixed to obtain the gradient-graded refractory filler. The preparation process of the nano-reinforced dispersion is as follows: each substance of the nano-reinforced phase, deionized water and dispersant are placed in an ultrasonic container for ultrasonic dispersion. The amount of deionized water added is 3-5 times the mass of the nano-reinforced phase. The dispersant is sodium dodecylbenzenesulfonate, and its added amount is 0.5-1wt% of the mass of the nano-reinforced phase. The ultrasonic power is 300-500W and the ultrasonic dispersion time is 20-30min, so that each substance is uniformly dispersed to obtain the nano-reinforced dispersion. The preparation process of the synergistic modifier is as follows: mica powder, talc powder, silica powder and hydroxypropyl methylcellulose are put into a mixer and stirred and mixed. The stirring temperature is room temperature, the stirring speed is 500-800 rpm, and the stirring time is 20-30 min, so that the substances are mixed evenly to obtain the synergistic modifier.

10. The method for preparing a high-temperature binder for multi-core assembly in the fabrication process of complex-structure ceramic cores according to claim 9, characterized in that, In step two, the addition rate of the gradient-graded refractory filler is 5-10 g / min, the stirring temperature is 25-35℃, the stirring speed is 600-800 rpm, and the stirring time is 40-60 min. In step three, after adding the nano-reinforced dispersion, continue stirring for 30-40 minutes; In step four, reduce the stirring speed to 400-600 rpm, add the synergistic modifier, and continue stirring for 20-30 minutes. In step five, the vacuum degassing process parameters for the high-temperature adhesive precursor are: vacuum degree of -0.08 to -0.09 MPa, degassing time of 15-25 min, and stirring once every 5 min during the vacuum degassing process, with each stirring lasting 5 min; the low-temperature curing process parameters for the high-temperature adhesive precursor are: curing temperature of 80-100℃, and curing time of 2-3 h.